Autism Spectrum Disorder in ICD-11: Diagnostic, Therapeutic and Identity - Related Implications of the Discontinuation of Asperger's Syndrome as a Separate Diagnosis - Dominika Gacka; Maksymilian Czarnota; Maria Wojcieszek; Aleksandra Żołnierek; Katarzyna Gondek; Magdalena Fidelis; Aleksandra Anna Mączyńska; Wiktoria Szumlińska; Noor Al-karawi; Paulina Kędziorek; Zuzanna Tanç (Journal of Education, Health and Sport, 2025)
The reclassification of Asperger’s syndrome within DSM-5 (2013) and ICD-11 (2019) marked a pivotal moment in the diagnostic landscape of neurodevelopmental disorders. After three decades of being recognized as a distinct clinical entity, Asperger’s syndrome was merged into the broader autism spectrum disorder (ASD) category, triggering extensive debate over diagnostic precision, social identity, and clinical consequences. This review synthesizes evidence on the evolution of diagnostic criteria, with a focus on historical milestones (Kanner, Asperger, Wing) that shaped the conceptualization of autism and Asperger’s syndrome across successive DSM and ICD editions. A structured literature search (PubMed, Scopus, Google Scholar; 2005–2024) identified 92 peer-reviewed articles meeting inclusion criteria (English or Polish language, human studies, and clear reference to diagnostic transitions and their psychosocial or clinical impact). Special attention is given to the effects of reclassification on individuals’ identity, the risk of diagnostic loss—especially in those with mild or atypical profiles—and the evolving terminology debate. Findings indicate that approximately 10–15% of individuals previously diagnosed with Asperger’s syndrome no longer meet ASD criteria under DSM-5 and ICD-11, raising concerns about service access and psychological well-being. The review also discusses challenges in distinguishing ASD from personality disorders, the diagnostic implications of camouflaging behaviors, and future research directions aimed at refining assessment tools and supporting neurodivergent identity.